Flexible self-supporting porous pole piece for ion battery, membrane assembly and preparation method of flexible self-supporting porous pole piece
By using ultra-high molecular weight polyethylene as a supporting framework and binder, combining active materials and conductive agents, flexible self-supporting porous electrode sheets and membrane modules are prepared, which solves the problems of insufficient conductivity and expansion of traditional binders and achieves high performance and safety of battery pole and membrane assembly.
Patent Information
- Application Number
- CN202411103998.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The binder of traditional ion batteries has weak conductivity, resulting in a degradation of performance, and is prone to expand during charging and discharging, and the process is complex and costly, making it difficult to promote on a large scale.
Ultra-high molecular weight polyethylene is used as the support framework, combined with active materials and conductive agents, and flexible self-supporting porous electrode sheets and membrane modules are prepared through extrusion-tensioning technology to form a network-surface contact structure to improve conductivity and mechanical properties.
It realizes that it is not easy to expand during charging and discharging, improves battery performance and safety, simplifies production processes, reduces costs, and enhances mechanical strength and conductivity.
Smart Images

Figure CN119133462A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible batteries, and in particular to a flexible self-supporting porous pole piece, a membrane assembly and a preparation method for an ion battery based on ultra-high molecular weight polyethylene. Background Art
[0002] In recent years, with the development of science and technology, people's demand for energy has continued to grow. Ion batteries (IBs) have become the main energy storage device in modern society and one of the important electronic basic products supporting the development of new smart terminals, electric vehicles, new energy storage and other industries. Ion batteries are secondary batteries composed of two reversibly embedded and de-embedded ionic compounds as positive and negative electrodes. When charging, ions are de-embedded from the positive electrode and embedded in the negative electrode, and vice versa when discharging.
[0003] Ion batteries (IBs) include lithium-ion batteries (LIBs), sodium-ion batteries (SIBs), zinc-ion batteries (ZIBs) and magnesium-ion batteries (MIBs). Looking at the history of battery development, we can see three characteristics of the current development of the world's battery industry. First, green and environmentally friendly batteries are developing rapidly, including ion batteries, nickel-hydrogen batteries, etc.; second, the transformation of primary batteries into batteries, which is in line with the sustainable development strategy; third, batteries are further developing in the direction of being small, light and thin. Among commercial rechargeable batteries, ion batteries have high specific energy, and the positive and negative electrodes are mainly composed of active materials, binders and conductive agents. In particular, lithium-ion batteries (LIBs) can achieve thin rechargeable batteries. Due to the particularity of the working principle of LIBs, they have special requirements for the structure of positive and negative electrode materials. With the development of lithium-ion battery technology, the importance of energy density indicators has increased day by day, and the electrode active load has gradually increased. Traditional binders have begun to expose shortcomings such as weak bonding, uneven distribution, insufficient mechanical strength, and uneven thickness of solid electrolyte interface (SEI). Therefore, the research on binders has gradually increased, and binders have begun to have some new functions (such as improving electrical conductivity, stabilizing interfaces, inhibiting the volume expansion of active materials, etc.), and the importance of developing new binders has become increasingly prominent.
[0004] In order to solve the above problems of traditional binders, domestic and foreign researchers have carried out a lot of research work in the past decade. Among them, modifying traditional binders or directly finding a new type of binder to replace traditional binders is one of the most effective means to improve the comprehensive performance of the pole piece, which can have high adhesion and high mechanical strength as well as the effect of inhibiting the expansion of the pole piece. The binder plays the role of bonding the active material to the current collector, the active material to the active material, and the active material to the conductive agent.
[0005] In ion batteries, the positive electrode binders mainly include oil-based polyvinylidene fluoride (PVDF), acrylic acid (PAA), polyacrylonitrile (PAN) and polyacrylate; the negative electrode binders are similar to the positive electrode, mainly including oil-based PVDF, water-based CMC, PAMAC, polyvinyl alcohol (PVA) and sodium alginate. The selection of binders is crucial when preparing positive and negative electrodes. Although the current binder process is relatively mature and has some excellent properties, such as PVDF has a wide electrochemical stability window and stable electrochemical performance at 0-5V (Li / Li+), and PVDF has good antioxidant ability and chemical reaction inertness, and is not easy to deteriorate, there are still some difficult to solve problems, such as: (1) The electronic and ionic conductivity of the binder itself is weak, which greatly reduces the performance of LIBs; (2) The bonding effect of some binders generally comes from the van der Waals force between molecules and the hydrogen bonds formed by the CF bonds on the main chain and other electrode substances. Especially when the binder is used in a silicon negative electrode with large volume expansion, it is easy to cause capacity loss and conductive network breakage; (3) Some binders require the use of N-methylpyrrolidone (NMP) as a solvent. This solvent has a high evaporation temperature, has certain environmental pollution, and is expensive; (4) The Young's modulus is relatively high, and the flexibility of the electrode is not good enough. In order to reduce the expansion problem of positive and negative electrodes during the charging and discharging process, the electrodes are currently prepared by methods such as binder cross-linking modification and surface high-temperature sintering to reduce their expansion ratio. There is no doubt that methods such as binder cross-linking modification overcome the expansion problem of positive and negative electrodes during the charging and discharging process and improve the charging and discharging performance of the electrodes, but this technical process is complex, costly and cannot be mass-produced, which hinders its large-scale promotion and application. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a flexible self-supporting porous electrode for an ion battery. The electrode has good flexibility and can maintain its performance after multiple foldings. At the same time, it can effectively avoid its expansion problem during the charging and discharging process. It has strong thermal stability and better absorption, wettability and adsorption of electrolyte. After application, it can effectively improve battery performance.
[0007] Another object of the present invention is to provide a membrane assembly for an ion battery having the above-mentioned flexible self-supporting porous electrode sheet.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned flexible self-supporting porous electrode.
[0009] Another object of the present invention is to provide a method for preparing the above-mentioned membrane assembly.
[0010] The technical solution of the present invention is: a flexible self-supporting porous electrode sheet for an ion battery, comprising a supporting skeleton, an active material and a conductive agent, wherein the supporting skeleton is a porous fiber membrane made of ultra-high molecular polyethylene, and the active material and the conductive agent are distributed on the surface of the supporting skeleton, and the overall thickness of the porous electrode sheet is 9 to 150 um; the porous electrode sheet is a porous positive electrode sheet or a porous negative electrode sheet, that is, the flexible self-supporting porous electrode sheet can be used as a porous positive electrode sheet or a negative electrode sheet, which can be achieved by using the corresponding type of active material.
[0011] In the porous electrode, the mass proportions of the various raw materials are as follows: 2 to 20 parts of ultra-high molecular weight polyethylene, 55 to 96 parts of active material, and 2 to 25 parts of conductive agent.
[0012] When the porous electrode sheet is a porous positive electrode sheet, the active material is a lithium ion battery positive electrode active material, a sodium ion battery positive electrode active material, a zinc ion battery positive electrode active material or a magnesium ion battery positive electrode active material; wherein the lithium ion battery positive electrode active material is one or more of lithium manganese oxide (LiMnO4), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4) or a ternary material (LiNiMnCoO2); the sodium ion battery positive electrode active material is sodium manganese oxide (NaMnO2), sodium cobalt oxide (NaCoO2), sodium nickel oxide (NaNiO 2), one or more of sodium iron phosphate (NaFePO4), sodium sulfide (Na2S) or sodium iron sulfide (Na2FeS2); the positive electrode active material of the zinc ion battery is one or more of manganese dioxide (MnO2), manganese oxide (Mn3O4), cobalt oxide (Co3O4) or lithium iron phosphate (LiFePO4); the positive electrode active material of the magnesium ion battery is one or more of manganese dioxide (MnO2), kaolin (KAlSi3O8), lithium iron phosphate (LiFePO4), molybdenum disulfide (MoS2) or titanium sulfide (TiS2);
[0013] When the porous electrode sheet is a porous negative electrode sheet, the active material is one or more of natural graphite, artificial graphite, soft carbon, hard carbon (HC), lithium titanate (LTO) or Si-based materials;
[0014] The particle size of the active material ranges from 50 nm to 10 μm.
[0015] The conductive agent is one or more of acetylene black (AB), graphite (KS), multi-walled carbon nanotubes, single-walled carbon nanotubes (CNTs), Ketjen black (KB) or graphene.
[0016] The present invention provides a membrane assembly for an ion battery having the above-mentioned flexible self-supporting porous electrode sheet, comprising a porous electrode sheet and a diaphragm layer connected to form an integrated structure, wherein the diaphragm layer is one layer and the porous electrode sheet is one or two layers;
[0017] When the porous electrode sheet is a single layer, the porous electrode sheet is a porous positive electrode sheet, and the porous positive electrode sheet and the diaphragm layer form a double-layer integrated membrane assembly, and the overall thickness of the double-layer integrated membrane assembly is 10 to 150 μm, wherein the thickness of the diaphragm layer is 1 to 20 μm, and the thickness of the porous positive electrode sheet is 9 to 130 μm;
[0018] When the porous electrode sheet has two layers, one of the porous electrode sheets is a porous positive electrode sheet, and the other layer is a porous negative electrode sheet. The porous positive electrode sheet, the diaphragm layer and the porous negative electrode sheet are sequentially connected to form a three-layer integrated membrane assembly. The overall thickness of the three-layer integrated membrane assembly is 19 to 280 μm, wherein the thickness of the diaphragm layer is 1 to 20 μm, the thickness of the porous positive electrode sheet is 9 to 130 μm, and the thickness of the porous negative electrode sheet is 9 to 130 μm.
[0019] Each layer of the double-layer integrated membrane assembly and the three-layer integrated membrane assembly uses a porous fiber membrane made of ultra-high molecular polyethylene as a supporting skeleton, and the surface of the supporting skeleton of the diaphragm layer is loaded with ceramic materials. In the double-layer integrated membrane assembly and the three-layer integrated membrane assembly, each layer is loaded with different functional materials, among which the porous pole piece is highly loaded with active materials and conductive agents, and the diaphragm is loaded with ceramic materials.
[0020] In the double-layer integrated membrane assembly or the three-layer integrated membrane assembly, the porosity of the porous positive electrode sheet and the porous negative electrode sheet are both 20-50%, and the porosity of the diaphragm layer is 40-80%.
[0021] In the double-layer integrated membrane assembly or the three-layer integrated membrane assembly, the molecular weight of the ultra-high molecular weight polyethylene used in the porous positive electrode plate and the porous negative electrode plate is 3 million to 9 million, and the molecular weight of the ultra-high molecular weight polyethylene used in the diaphragm layer is 800,000 to 2.5 million.
[0022] In the diaphragm layer, the mass fractions of each raw material are: 50 to 99 parts of ultra-high molecular weight polyethylene and 1 to 50 parts of ceramic material;
[0023] The ceramic material is one or more of silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and titanium dioxide (TiO2), and the particle size of the ceramic material ranges from 5nm to 100nm.
[0024] The present invention provides a method for preparing the above-mentioned flexible self-supporting porous electrode sheet, comprising the following steps:
[0025] (1) adding active material, ultra-high molecular weight polyethylene, conductive agent and diluent into a stirring tank according to a preset ratio and stirring evenly, and then continuously plasticizing and melt-blending through an extruder to form a homogeneous solution, extruding through a single-layer film mold, and cooling and shaping through a casting roller to form a single-layer gel film; wherein the roller temperature of the casting roller is 10 to 50° C.;
[0026] (2) subjecting the single-layer gel film obtained in step (1) to uniaxial stretching, asynchronous biaxial stretching or synchronous biaxial stretching, and then to heat setting to obtain a stretched fiber gel film having an ultra-high molecular weight polyethylene fiber skeleton; wherein the stretching temperature is 90-130° C., the transverse to longitudinal stretching ratio or the longitudinal stretching ratio is 1 to 10 times, the heat setting temperature is 90 to 130° C., and the heat setting time is 0.5 to 10 minutes;
[0027] (3) using an extractant to remove the diluent in the stretched fiber gel membrane obtained in step (2), then drying it, and then performing high-temperature annealing to obtain a porous electrode; wherein the high-temperature annealing temperature is 130 to 160° C., and the annealing time is 1 to 8 minutes.
[0028] The present invention provides a method for preparing a membrane assembly for the above-mentioned ion battery, comprising the following steps:
[0029] (1) adding active material, ultra-high molecular weight polyethylene, conductive agent and diluent into a stirring tank according to a preset ratio, stirring evenly, and then continuously plasticizing and melt blending through an extruder to form a porous electrode homogeneous solution; adding ceramic material, ultra-high molecular weight polyethylene and diluent into a stirring tank according to a preset ratio, stirring evenly, and then continuously plasticizing and melt blending through an extruder to form a diaphragm layer homogeneous solution; then co-extruding through a multi-layer film mold, cooling and shaping through a casting roller to form a multi-layer gel film; wherein the roller temperature of the casting roller is 10 to 50° C.;
[0030] (2) subjecting the multilayer gel film obtained in step (1) to uniaxial stretching, asynchronous biaxial stretching or synchronous biaxial stretching, and then to heat setting to obtain a stretched fiber gel film having an ultra-high molecular weight polyethylene fiber skeleton; wherein the stretching temperature is 90-130° C., the transverse to longitudinal stretching ratio or the longitudinal stretching ratio is 1 to 10 times, the heat setting temperature is 90 to 130° C., and the heat setting time is 0.5 to 10 minutes;
[0031] (3) using an extractant to remove the diluent in the stretched fiber gel membrane obtained in step (2), then drying, and then high-temperature annealing to obtain a membrane assembly; wherein the high-temperature annealing temperature is 130 to 160° C., and the annealing time is 1 to 8 minutes.
[0032] In the above method, when preparing a double-layer integrated membrane component, in step (1), the raw materials of the porous positive electrode plate are continuously plasticized and melt-blended by one extruder, and the raw materials of the diaphragm layer are continuously plasticized and melt-blended by another extruder. Correspondingly, the multi-layer mold used for co-extrusion is a double-layer mold; when preparing a three-layer integrated membrane component, in step (1), the raw materials of the porous positive electrode plate are continuously plasticized and melt-blended by the first extruder, the raw materials of the porous negative electrode plate are continuously plasticized and melt-blended by the second extruder, and the raw materials of the diaphragm layer are continuously plasticized and melt-blended by the third extruder. Correspondingly, the multi-layer mold used for co-extrusion is a three-layer mold.
[0033] In the step (1), in the porous electrode homogeneous solution or the diaphragm layer homogeneous solution formed after mixing, the mass of the diluent accounts for 50 to 90% of the total mass of the blend formed after mixing; the diluent can be a polymer diluent (such as PVP, PEG, PVA, etc.) or a small molecule diluent (such as decahydronaphthalene, mineral oil, vegetable oil, etc.).
[0034] In the flexible self-supporting porous pole piece, membrane assembly and preparation method for the above-mentioned ion battery, the principle is: the porous pole piece uses ultra-high molecular weight polyethylene as a binder, and due to its affinity with active materials and conductive agents, it is mixed evenly, which can extend the life of IBs. At the same time, in the ultra-high molecular polyethylene fiber membrane skeleton formed during extrusion after blending, the active material and the conductive agent are adhered to form a network-surface contact, so that it forms a more uniform, more stable and thinner SEI layer during the charge and discharge cycle, which greatly improves the cycle performance of the ion battery. Among them, the self-supporting ultra-high molecular polyethylene fiber membrane skeleton has a three-dimensional porous mesh structure, so that the electrochemical active sites of the active material attached to its surface are fully exposed as much as possible, and it has a large specific surface area, which can effectively improve the electron transmission of the active material with poor conductivity, promote the effective transmission of carriers in the catalytic process, and form a strong interaction between the active material and the substrate (i.e., the supporting skeleton). The strong contact interface between the active material and the self-supporting substrate can efficiently transmit electrons and reduce the reaction barrier. In its preparation method, the porous electrode and the diaphragm layer are compounded together by co-extrusion, which greatly reduces the production process and reduces the surface resistance. At the same time, through the extrusion-stretching technology, the thickness of the porous electrode and the membrane assembly, and the distribution of the microporous structure in the porous electrode and the membrane assembly can be adjusted, so as to better obtain flexible battery electrodes and membrane assemblies that meet the requirements.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The flexible self-supporting porous pole piece, membrane assembly and preparation method for the ion battery are proposed to solve the problems of low conductivity, poor electrolyte wettability, low mechanical strength, complex process and high cost in the manufacturing process of the existing positive and negative pole pieces and membrane batteries of polymer ion batteries. Ultra-high molecular weight polyolefin (UHMWPE) is used as a binder, and the flexible self-supporting porous pole piece and the membrane assembly of the pole piece and the diaphragm are prepared by the extrusion-stretching molding method. A strong interaction can be formed between the active material and the substrate (i.e., the supporting skeleton). The strong contact interface between the active material and the self-supporting substrate can efficiently transmit electrons and reduce the reaction barrier. At the same time, due to the strong contact between the active material and the self-supporting substrate, the deficiency of easy detachment during the catalytic process of using the binder is avoided, so it shows good catalytic stability, forming a new flexible battery and its manufacturing method, which will better enhance the advantages of the performance of the flexible battery.
[0037] In the flexible self-supporting porous electrode piece, membrane assembly and preparation method for the present ion battery, the porous electrode piece uses ultra-high molecular weight polyethylene as a binder and is formed with active materials and conductive agents through a preferred ratio and molding process. The ultra-high molecular weight polyethylene plays a role of mechanical support, enhancing the mechanical properties and stability of the porous electrode piece; and the membrane assembly also uses ultra-high molecular weight polyethylene as a substrate (that is, the diaphragm layer and the porous electrode piece are both made of ultra-high molecular weight polyethylene as their supporting structure), and the porous electrode piece and the diaphragm layer are compounded together by co-extrusion, which greatly reduces the production process and reduces the surface resistance. In the preparation method thereof, a diluent is used in the extraction process to form a microporous structure in the porous pole piece and the membrane assembly, thereby increasing the specific surface area of the porous pole piece and the membrane assembly, being able to store more electrolyte, and improving the performance of the battery. At the same time, the porous pole piece and the membrane assembly can completely not cause a great impact on the performance of the battery after folding and puncturing, greatly improving the safety performance of the battery, and can completely meet the requirements of ionic conductivity of the polymer ion battery pole piece and the membrane assembly; in addition, in the preparation method of the porous pole piece and the membrane assembly, the thickness of the battery pole piece and the membrane assembly, and the distribution of the microporous structure in the battery pole piece and the membrane assembly are adjustable through the extrusion-stretching technology, so as to better obtain a flexible battery pole piece and membrane assembly that meets the requirements. At the same time, under the conditions of the thickness and main components of the porous pole piece and the membrane assembly itself, it can completely meet the requirement that the battery performance is not affected after multiple foldings.
[0038] In the flexible self-supporting porous pole piece and membrane assembly used in the ion battery, due to the characteristics of ultra-high molecular weight polyethylene, it has affinity with active materials and conductive agents, making them mixed evenly and extending the life of IBs. At the same time, the ultra-high molecular polyethylene fiber membrane skeleton formed during the co-extrusion adheres to the active materials and conductive agents to form a network-surface contact, so that it forms a more uniform, more stable and thinner SEI layer during the charge and discharge cycle, greatly improving the cycle performance of the ion battery. The self-supporting ultra-high molecular polyethylene fiber membrane skeleton has a three-dimensional porous mesh structure, so that the electrochemical active sites of the active materials attached to its surface are fully exposed as much as possible, and has a large specific surface area, which can effectively improve the electron transmission of active materials with poor conductivity, promote the effective transmission of carriers in the catalytic process, and form a strong interaction between the active material and the substrate. The strong contact interface between the active material and the self-supporting substrate can efficiently transmit electrons and reduce the reaction barrier. Among them, the self-supporting characteristics can make the mesh current collector or directly use the coating method to apply the conductive agent to the electrode surface to form a conductive layer, which can greatly reduce the energy density of the ion battery and reduce the weight of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is an electron microscope image of the cross-sectional structure of the porous positive electrode sheet prepared in Example 1.
[0040] Figure 2 This is an electron microscope image of the cross-sectional structure of the porous positive electrode sheet prepared in Example 1 after 200 cycles.
[0041] Figure 3 This is an electron microscope image of the cross-sectional structure of the porous positive electrode sheet prepared in Example 2.
[0042] Figure 4 This is an electron microscope image of the cross-sectional structure of the porous positive electrode sheet prepared in Example 2 after 200 cycles.
[0043] Figure 5 This is an electron microscope image of the cross-sectional structure of the porous negative electrode sheet prepared in Example 3.
[0044] Figure 6 This is a cross-sectional structural diagram of the membrane assembly prepared in Example 4.
[0045] Figure 7 This is an electron microscope image of the cross-sectional structure of a conventional electrode prepared as a comparative example. DETAILED DESCRIPTION
[0046] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0047] Example 1
[0048] This embodiment provides a flexible self-supporting porous positive electrode sheet for an ion battery and a preparation method thereof.
[0049] The porous positive electrode plate includes a supporting skeleton, an active material and a conductive agent. The supporting skeleton is a porous fiber membrane made of ultra-high molecular polyethylene. The active material and the conductive agent are distributed on the surface of the supporting skeleton. The overall thickness of the porous electrode plate is 9 to 150 um. Among them, the mass fractions of each raw material are as follows: 2 to 20 parts of ultra-high molecular weight polyethylene, 55 to 96 parts of active materials, and 2 to 25 parts of conductive agents. The active material can be a lithium-ion battery positive electrode active material, a sodium-ion battery positive electrode active material, a zinc-ion battery positive electrode active material, or a magnesium-ion battery positive electrode active material; among them, the lithium-ion battery positive electrode active material is one or more of lithium manganese oxide (LiMnO4), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4) or a ternary material (LiNiMnCoO2); the sodium-ion battery positive electrode active material is sodium manganese oxide (NaMnO2), sodium cobalt oxide (NaCoO2), sodium nickel oxide (NaNiO2), sodium iron phosphate (NaFePO4 ), sodium sulfide (Na2S) or sodium iron sulfide (Na2FeS2); the positive electrode active material of the zinc ion battery is one or more of manganese dioxide (MnO2), manganese oxide (Mn3O4), cobalt oxide (Co3O4) or lithium iron phosphate (LiFePO4); the positive electrode active material of the magnesium ion battery is one or more of manganese dioxide (MnO2), kaolin (KAlSi3O8), lithium iron phosphate (LiFePO4), molybdenum disulfide (MoS2) or titanium sulfide (TiS2); the particle size range of the active material is 50nm to 10μm. The conductive agent can be one or more of acetylene black (AB), graphite (KS), multi-walled carbon nanotubes, single-walled carbon nanotubes (CNTs), Ketjen black (KB) or graphene.
[0050] In this embodiment, the method for preparing the porous positive electrode sheet is as follows:
[0051] (1) The fiber skeleton is made of ultra-high molecular weight polyethylene with a molecular weight of 7.8 million, the positive electrode active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (Super P), and the diluent is liquid paraffin;
[0052] Lithium iron phosphate, ultra-high molecular weight polyethylene and conductive carbon black were weighed in a mass ratio of 80:10:10, and liquid paraffin was added to form a mixture, wherein the mass of the liquid paraffin accounted for 80% of the total mass of the mixture, and the mixture was stirred in a stirred tank at 80° C. for 5 minutes to be uniformly stirred;
[0053] (2) at 200° C., the mixture is melt-blended and plasticized by a twin-screw extruder, and a single-layer gel film is cast by an extrusion die, and the single-layer gel film is then biaxially stretched to form a stretched fiber gel film, wherein the stretching ratio is 3×3 and the stretching temperature is 110° C. After the stretching is completed, heat setting is performed at 120° C. for 5 minutes;
[0054] (3) using n-hexane as an extraction liquid to extract the stretched fiber gel membrane after heat setting in step (2) to remove the liquid paraffin to form a microporous structure;
[0055] (4) Drying to remove n-hexane, and annealing at a high temperature of 140° C. for 3 min to obtain a flexible self-supporting porous positive electrode sheet for a lithium-ion battery.
[0056] The cross-sectional SEM image of the flexible self-supporting porous positive electrode sheet of the lithium-ion battery obtained by the above preparation method is as follows: Figure 1 As shown in the figure, the thickness is 35 μm, the tensile strength is 4.23 MPa, and the conductivity is 2.45×10 -3 S / cm. After assembling the battery, a cycle test was performed, such as Figure 2 Shown is a cross-sectional SEM image of the obtained flexible self-supporting lithium-ion battery porous positive electrode sheet after 200 cycles.
[0057] Example 2
[0058] The present embodiment provides a flexible self-supporting porous positive electrode sheet for an ion battery and a preparation method thereof.
[0059] The porous positive electrode plate includes a supporting skeleton, an active material and a conductive agent. The supporting skeleton is a porous fiber membrane made of ultra-high molecular polyethylene. The active material and the conductive agent are distributed on the surface of the supporting skeleton. The overall thickness of the porous electrode plate is 9 to 150 um. Among them, the mass fractions of each raw material are as follows: 2 to 20 parts of ultra-high molecular weight polyethylene, 55 to 96 parts of active materials, and 2 to 25 parts of conductive agents. The active material can be a lithium-ion battery positive electrode active material, a sodium-ion battery positive electrode active material, a zinc-ion battery positive electrode active material, or a magnesium-ion battery positive electrode active material; among them, the lithium-ion battery positive electrode active material is one or more of lithium manganese oxide (LiMnO4), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4) or a ternary material (LiNiMnCoO2); the sodium-ion battery positive electrode active material is sodium manganese oxide (NaMnO2), sodium cobalt oxide (NaCoO2), sodium nickel oxide (NaNiO2), sodium iron phosphate (NaFePO4 ), sodium sulfide (Na2S) or sodium iron sulfide (Na2FeS2); the positive electrode active material of the zinc ion battery is one or more of manganese dioxide (MnO2), manganese oxide (Mn3O4), cobalt oxide (Co3O4) or lithium iron phosphate (LiFePO4); the positive electrode active material of the magnesium ion battery is one or more of manganese dioxide (MnO2), kaolin (KAlSi3O8), lithium iron phosphate (LiFePO4), molybdenum disulfide (MoS2) or titanium sulfide (TiS2); the particle size range of the active material is 50nm to 10μm. The conductive agent can be one or more of acetylene black (AB), graphite (KS), multi-walled carbon nanotubes, single-walled carbon nanotubes (CNTs), Ketjen black (KB) or graphene.
[0060] In this embodiment, the method for preparing the porous positive electrode sheet is as follows:
[0061] (1) The fiber skeleton is made of ultra-high molecular weight polyethylene with a molecular weight of 7.8 million, the positive electrode active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (Super P), and the diluent is liquid paraffin;
[0062] Lithium iron phosphate, ultra-high molecular weight polyethylene and conductive carbon black were weighed in a mass ratio of 80:10:10, and liquid paraffin was added to form a mixture, wherein the mass of the liquid paraffin accounted for 80% of the total mass of the mixture, and the mixture was stirred in a stirred tank at 80° C. for 5 minutes to be uniformly stirred;
[0063] (2) at 200° C., melt-blending and plasticizing the mixture through a twin-screw extruder, casting through an extrusion die to obtain a single-layer gel film, and then uniaxially stretching the single-layer gel film to form a stretched fiber gel film, wherein the stretching ratio is 3 and the stretching temperature is 110° C.; after the stretching is completed, heat setting is performed at 120° C. for 5 minutes;
[0064] (3) using n-hexane as an extraction liquid to extract the stretched fiber gel membrane after heat setting in step (2) to remove the liquid paraffin to form a microporous structure;
[0065] (4) Drying to remove the n-hexane, and annealing at a high temperature of 140° C. for 3 min to obtain a flexible self-supporting porous positive electrode sheet for a lithium-ion battery.
[0066] The cross-sectional SEM image of the flexible self-supporting porous positive electrode sheet of the lithium-ion battery obtained by the above preparation method is as follows: Figure 3 As shown in the figure, the thickness is 102 μm, the tensile strength is 3.5 MPa, and the conductivity is 5.47×10 -3 S / cm. After assembling the battery, a cycle test was performed, such as Figure 4 Shown is a cross-sectional SEM image of the obtained flexible self-supporting lithium-ion battery porous positive electrode sheet after 200 cycles.
[0067] Example 3
[0068] The present embodiment provides a flexible self-supporting porous negative electrode sheet for an ion battery and a preparation method thereof.
[0069] The porous negative electrode plate includes a supporting skeleton, an active material and a conductive agent. The supporting skeleton is a porous fiber membrane made of ultra-high molecular polyethylene. The active material and the conductive agent are distributed on the surface of the supporting skeleton. The overall thickness of the porous electrode plate is 9 to 150um. Among them, the mass fractions of each raw material are as follows: 2 to 20 parts of ultra-high molecular weight polyethylene, 55 to 96 parts of active materials, and 2 to 25 parts of conductive agents. The active material can be one or more of natural graphite, artificial graphite, soft carbon, hard carbon (HC), lithium titanate (LTO) or Si-based materials; the particle size range of the active material is 50nm to 10μm. The conductive agent can be one or more of acetylene black (AB), graphite (KS), multi-walled carbon nanotubes, single-walled carbon nanotubes (CNTs), Ketjen black (KB) or graphene.
[0070] In this embodiment, the method for preparing the porous negative electrode sheet is as follows:
[0071] (1) The fiber skeleton is made of ultra-high molecular weight polyethylene with a molecular weight of 9 million, the negative electrode active material is graphite, the conductive agent is conductive carbon black (Super P), and the diluent is liquid paraffin;
[0072] Graphite, ultra-high molecular weight polyethylene and conductive carbon black were weighed in a mass ratio of 80:10:10, and liquid paraffin was added to form a mixture, wherein the mass of the liquid paraffin accounted for 80% of the total mass of the mixture, and the mixture was stirred in a stirred tank at 80° C. for 20 minutes to be uniformly stirred;
[0073] (2) at 200° C., the mixture is melt-blended and plasticized by a twin-screw extruder, and a single-layer gel film is cast by an extrusion die, and the single-layer gel film is then biaxially stretched to form a stretched fiber gel film, wherein the stretching ratio is 2×2 and the stretching temperature is 110° C. After the stretching is completed, heat setting is performed at 120° C. for 5 minutes;
[0074] (3) using n-hexane as an extraction liquid to extract the stretched fiber gel membrane after heat setting in step (2) to remove the liquid paraffin to form a microporous structure;
[0075] (4) Drying to remove the n-hexane, and annealing at a high temperature of 150° C. for 2 min to obtain a flexible self-supporting porous negative electrode sheet for a lithium-ion battery.
[0076] The cross-sectional SEM image of the flexible self-supporting porous negative electrode sheet of the lithium-ion battery obtained by the above preparation method is as follows: Figure 5 As shown in the figure, the thickness is 98 μm, the tensile strength is 3.16 MPa, and the conductivity is 2.45×10 -3 S / cm.
[0077] Example 4
[0078] This embodiment provides a membrane assembly for an ion battery and a method for preparing the same.
[0079] The membrane assembly of this embodiment is a double-layer integrated membrane assembly, including a porous positive electrode plate and a diaphragm layer connected to form an integrated structure. The overall thickness of the double-layer integrated membrane assembly is 10 to 150 μm, of which the thickness of the diaphragm layer is 1 to 20 μm, and the thickness of the porous positive electrode plate is 9 to 130 μm; in the membrane assembly, each layer uses a porous fiber membrane made of ultra-high molecular polyethylene as a supporting skeleton, but each layer loads different functional materials, among which the porous electrode plate is highly loaded with active materials and conductive agents, and the diaphragm is loaded with ceramic materials. The porosity of the porous positive electrode plate is 20 to 50%, and the porosity of the diaphragm layer is 40 to 80%. The molecular weight of the ultra-high molecular weight polyethylene used in the porous positive electrode plate is 3 million to 9 million, and the molecular weight of the ultra-high molecular weight polyethylene used in the diaphragm layer is 800,000 to 2.5 million. In the diaphragm layer, the mass proportions of each raw material are: 50 to 99 parts of ultra-high molecular weight polyethylene and 1 to 50 parts of ceramic material; the ceramic material is one or more of silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and titanium dioxide (TiO2), and the particle size range of the ceramic material is 5nm to 100nm.
[0080] In this embodiment, the preparation method of the membrane assembly is as follows:
[0081] (1) In the porous positive electrode sheet, the fiber skeleton is made of ultra-high molecular weight polyethylene with a molecular weight of 7.8 million, the positive electrode active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (Super P), and the diluent is liquid paraffin;
[0082] In the diaphragm layer, the fiber skeleton is made of ultra-high molecular weight polyethylene with a molecular weight of 1.8 million, the inorganic ceramic particles are gas-phase SiO2, and the diluent is liquid paraffin;
[0083] Preparation of a porous electrode mixture: lithium iron phosphate, ultra-high molecular weight polyethylene and conductive carbon black are weighed in a mass ratio of 80:10:10, and liquid paraffin is added to form a porous electrode mixture, wherein the mass of the liquid paraffin accounts for 80% of the total mass of the porous electrode mixture formed. The porous electrode mixture is stirred in a stirring tank at 80° C. for 20 minutes and stirred evenly;
[0084] Preparation of a diaphragm layer mixture: SiO2, ultra-high molecular weight polyethylene and conductive carbon black were weighed in a mass ratio of 80:20, and liquid paraffin was added to form a diaphragm layer mixture, wherein the mass of the liquid paraffin accounted for 80% of the total mass of the diaphragm layer mixture formed, and the diaphragm layer mixture was stirred in a stirring tank at 80° C. for 5 minutes to be uniformly stirred;
[0085] (2) at 200°C, the porous electrode mixture and the diaphragm layer mixture are melt-blended and plasticized by two twin-screw extruders, and then cast by a multi-layer co-extrusion die to obtain a double-layer gel film, and then the double-layer gel film is biaxially stretched to obtain a stretched fiber gel film, wherein the stretching ratio is 4×4 and the stretching temperature is 110°C; after the stretching is completed, heat setting is performed at 120°C for 5 minutes;
[0086] (3) using n-hexane as an extraction liquid to extract the stretched fiber gel membrane after heat setting in step (2) to remove the liquid paraffin to form a microporous structure;
[0087] (4) drying to remove the n-hexane, and performing an annealing treatment at a high temperature of 150° C. for 2 min to obtain a double-layer integrated membrane assembly of a porous positive electrode sheet and a separator layer;
[0088] The cross-sectional SEM image of the double-layer integrated membrane assembly obtained by the above preparation method is as follows: Figure 6 As shown in the figure, the membrane component has a thickness of 180 μm, a tensile strength of 50.4 MPa, and a conductivity of 2.45×10 -3 S / cm.
[0089] Comparative Example
[0090] This comparative example provides a conventional dry method for preparing a positive electrode sheet using polyvinylidene fluoride as a binder, as follows:
[0091] (1) Polyvinylidene fluoride (PVDF) is used as a binder, lithium iron phosphate (LiFePO4) is used as a positive electrode active material, and conductive carbon black (Super P) is used as a conductive agent;
[0092] Lithium iron phosphate, polyvinylidene fluoride and conductive carbon black are weighed according to a mass ratio of 80:10:10, and then 50% of lithium iron phosphate, conductive carbon black, binder PVDF and 50% of lithium iron phosphate are added to the mixer in sequence. The revolution speed is maintained at (5±1) r / min during the feeding process. After the feeding is completed, dry mixing pre-stirring is started, and the revolution is set to reverse speed (7±1) r / min. The rotation dispersion is temporarily not started. After 5 minutes, normal dry mixing is started, and the revolution speed is set to (13±1) r / min and the rotation speed is (400±2) r / min. Stir for 0.5h. This process needs to ensure that the dry mixing can fully mix the lithium iron phosphate, conductive carbon black and binder PVDF powders;
[0093] (2) spraying the evenly dispersed powder with N-methylpyrrolidone (NMP) solvent, first adding part of the NMP solvent, controlling it to about 70% of the total amount of the NMP solvent; then entering the powder wetting step, mainly by revolution stirring, setting the revolution speed to (15±5) r / min, supplemented by (150±2) r / min, stirring for 1.5 hours, at which time the slurry presents a thick liquid with a relatively high viscosity, adding the remaining NMP solvent, diluting and stirring for 10-15 minutes;
[0094] (3) Entering the high-speed dispersion and viscosity reduction step: maintaining the revolution speed at (15±5) r / min, increasing the autogenous dispersion speed to (1200±50) r / min, stirring for 2 h, slowing down the stirring (revolution speed (10±1) r / min, autogenous speed (200±5) r / min) to cool down, and completing the slurry preparation;
[0095] (4) applying the slurry obtained in step (3) onto a foil material, and evenly scraping the slurry with a scraper, then placing the scraped aluminum foil in a blast oven to dry for 10 hours, and punching it into a suitable size;
[0096] (5) The electrode piece processed in step (4) is placed in a vacuum oven and dried for 2 hours to remove excess moisture, and then stored dry in an inert atmosphere for later use to obtain an LFP positive electrode.
[0097] The cross-sectional SEM image of the positive electrode sheet with polyvinylidene fluoride as a binder obtained by the above preparation method is as follows Figure 7 As shown in the figure, the thickness is 48.56 μm, the tensile strength is 2.4 MPa, and the conductivity is 2.45×10 -3 s / cm.
[0098] The porous positive electrode sheets, negative electrode sheets or membrane assemblies prepared in the above-mentioned Examples 1-4 and the positive electrode sheets prepared in the comparative example are assembled into a full battery according to the battery assembly process, and the electrochemical properties of the battery are tested at room temperature and 1C, and the charge and discharge voltage is set to 2.5-4.3V. The electrochemical performance test results are shown in Table 1.
[0099] Table 1. Electrochemical performance test results of samples in various embodiments and comparative examples
[0100]
[0101] As can be seen from Table 1, in the present application, ultra-high molecular polyethylene is used as the substrate, and a fiber skeleton with a porous structure is used as the supporting structure. After being stretched, the fiber skeleton can provide excellent mechanical properties for the finally formed flexible self-supporting porous electrode and multilayer membrane battery; at the same time, active materials and conductive agents are loaded on the surface of the fiber skeleton of the porous electrode to form a network-surface contact, which can effectively inhibit the occurrence of cracks in the electrode during the charging and discharging process; a diluent is used to form micropores in the electrode during the extraction and drying process, thereby increasing the specific surface area of the electrode, being able to store more electrolyte, and improving the performance of the battery; the membrane assembly is composited with a diaphragm layer on the basis of the porous electrode preparation method, which greatly simplifies the preparation method, and the porous electrode and the diaphragm layer are on the same substrate, so that they are in good contact with each other, reducing the internal resistance of the battery, and under the conditions of the thickness of the electrode itself and the main components, it can fully meet the requirement of not affecting the battery performance under multiple folding, thereby improving the safety performance.
[0102] As described above, the present invention can be better implemented. The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention; that is, all equivalent changes and modifications made according to the content of the present invention are covered by the scope of protection required by the claims of the present invention.
Claims
1. A flexible self-supporting porous electrode for an ion battery, characterized in that: It includes a supporting skeleton, active materials and a conductive agent. The supporting skeleton is a porous fiber membrane made of ultra-high molecular polyethylene. The active materials and the conductive agent are distributed on the surface of the supporting skeleton. The overall thickness of the porous electrode is 9 to 150 um. The porous electrode is a porous positive electrode or a porous negative electrode.
2. A flexible self-supporting porous electrode for an ion battery according to claim 1, characterized in that: In the porous electrode, the mass proportions of the raw materials are as follows: 2 to 20 parts of ultra-high molecular weight polyethylene, 55 to 96 parts of active material, and 2 to 25 parts of conductive agent.
3. The flexible self-supporting porous electrode sheet for an ion battery according to claim 1, characterized in that: When the porous electrode sheet is a porous positive electrode sheet, the active material is a lithium ion battery positive electrode active material, a sodium ion battery positive electrode active material, a zinc ion battery positive electrode active material or a magnesium ion battery positive electrode active material; wherein the lithium ion battery positive electrode active material is one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate or a ternary material; the sodium ion battery positive electrode active material is one or more of sodium manganese oxide, sodium cobalt oxide, sodium nickel oxide, sodium iron phosphate, sodium sulfide or sodium iron sulfide; the zinc ion battery positive electrode active material is one or more of manganese dioxide, manganese oxide, cobalt oxide or lithium iron phosphate; the magnesium ion battery positive electrode active material is one or more of manganese dioxide, kaolin, lithium iron phosphate, molybdenum disulfide or titanium sulfide; When the porous electrode sheet is a porous negative electrode sheet, the active material is one or more of natural graphite, artificial graphite, soft carbon, hard carbon, lithium titanate or Si-based materials; The particle size of the active material ranges from 50 nm to 10 μm.
4. The flexible self-supporting porous electrode sheet for an ion battery according to claim 1, characterized in that: The conductive agent is one or more of acetylene black, graphite, multi-walled carbon nanotubes, single-walled carbon nanotubes, Ketjen black or graphene.
5. A membrane assembly for an ion battery having the flexible self-supporting porous electrode sheet according to any one of claims 1 to 4, characterized in that: It includes a porous electrode piece and a diaphragm layer connected to form an integrated structure, wherein the diaphragm layer is one layer and the porous electrode piece is one or two layers; When the porous electrode sheet is a single layer, the porous electrode sheet is a porous positive electrode sheet, and the porous positive electrode sheet and the diaphragm layer form a double-layer integrated membrane assembly, and the overall thickness of the double-layer integrated membrane assembly is 10 to 150 μm, wherein the thickness of the diaphragm layer is 1 to 20 μm, and the thickness of the porous positive electrode sheet is 9 to 130 μm; When the porous electrode sheet has two layers, one of the porous electrode sheets is a porous positive electrode sheet, and the other layer is a porous negative electrode sheet. The porous positive electrode sheet, the diaphragm layer and the porous negative electrode sheet are sequentially connected to form a three-layer integrated membrane assembly. The overall thickness of the three-layer integrated membrane assembly is 19 to 280 μm, wherein the thickness of the diaphragm layer is 1 to 20 μm, the thickness of the porous positive electrode sheet is 9 to 130 μm, and the thickness of the porous negative electrode sheet is 9 to 130 μm. Each layer of the double-layer integrated membrane assembly and the three-layer integrated membrane assembly uses a porous fiber membrane made of ultra-high molecular polyethylene as a supporting skeleton, wherein the surface of the supporting skeleton of the diaphragm layer is loaded with ceramic material.
6. The membrane assembly for an ion battery according to claim 5, characterized in that: In the double-layer integrated membrane assembly or the three-layer integrated membrane assembly, the porosity of the porous positive electrode sheet and the porous negative electrode sheet are both 20-50%, and the porosity of the diaphragm layer is 40-80%.
7. The membrane assembly for an ion battery according to claim 5, characterized in that: In the double-layer integrated membrane assembly or the three-layer integrated membrane assembly, the molecular weight of the ultra-high molecular weight polyethylene used in the porous positive electrode plate and the porous negative electrode plate is 3 million to 9 million, and the molecular weight of the ultra-high molecular weight polyethylene used in the diaphragm layer is 800,000 to 2.5 million.
8. The membrane assembly for an ion battery according to claim 5, characterized in that: In the diaphragm layer, the mass fractions of each raw material are: 50 to 99 parts of ultra-high molecular weight polyethylene and 1 to 50 parts of ceramic material; The ceramic material is one or more of silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and titanium dioxide (TiO2), and the particle size of the ceramic material ranges from 5nm to 100nm.
9. A method for preparing the flexible self-supporting porous electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding active material, ultra-high molecular weight polyethylene, conductive agent and diluent into a stirring tank according to a preset ratio and stirring evenly, and then continuously plasticizing and melt-blending through an extruder to form a homogeneous solution, extruding through a single-layer film mold, and cooling and shaping through a casting roller to form a single-layer gel film; wherein the roller temperature of the casting roller is 10 to 50° C.; (2) subjecting the single-layer gel film obtained in step (1) to uniaxial stretching, asynchronous biaxial stretching or synchronous biaxial stretching, and then to heat setting to obtain a stretched fiber gel film having an ultra-high molecular weight polyethylene fiber skeleton; wherein the stretching temperature is 90-130° C., the transverse to longitudinal stretching ratio or the longitudinal stretching ratio is 1 to 10 times, the heat setting temperature is 90 to 130° C., and the heat setting time is 0.5 to 10 minutes; (3) using an extractant to remove the diluent in the stretched fiber gel membrane obtained in step (2), then drying it, and then performing high-temperature annealing to obtain a porous electrode; wherein the high-temperature annealing temperature is 130 to 160° C., and the annealing time is 1 to 8 minutes.
10. A method for preparing a membrane assembly for an ion battery according to any one of claims 5 to 8, characterized in that: The following steps are involved: (1) adding active material, ultra-high molecular weight polyethylene, conductive agent and diluent into a stirring tank according to a preset ratio, stirring evenly, and then continuously plasticizing and melt blending through an extruder to form a porous electrode homogeneous solution; adding ceramic material, ultra-high molecular weight polyethylene and diluent into a stirring tank according to a preset ratio, stirring evenly, and then continuously plasticizing and melt blending through an extruder to form a diaphragm layer homogeneous solution; then co-extruding through a multi-layer film mold, cooling and shaping through a casting roller to form a multi-layer gel film; wherein the roller temperature of the casting roller is 10 to 50° C.; (2) subjecting the multilayer gel film obtained in step (1) to uniaxial stretching, asynchronous biaxial stretching or synchronous biaxial stretching, and then to heat setting to obtain a stretched fiber gel film having an ultra-high molecular weight polyethylene fiber skeleton; wherein the stretching temperature is 90-130° C., the transverse to longitudinal stretching ratio or the longitudinal stretching ratio is 1 to 10 times, the heat setting temperature is 90 to 130° C., and the heat setting time is 0.5 to 10 minutes; (3) using an extractant to remove the diluent in the stretched fiber gel membrane obtained in step (2), then drying, and then high-temperature annealing to obtain a membrane assembly; wherein the high-temperature annealing temperature is 130 to 160° C., and the annealing time is 1 to 8 minutes.
Citation Information
Patent Citations
Flexible lithium ion battery electrode plate with self supporting capability and preparation method thereof
CN105633343A
Flexible polymer thin lithium ion battery and preparation method thereof
CN106784993A
Porous pole piece manufacturing method and lithium ion battery
CN116111049A
Porous self-supporting flexible thick electrode and preparation method thereof
CN116682926A
Porous film, separator for lithium battery using the same, and battery
JP2010111833A
Cited By
Electrode, energy storage device, electrode production system and electrode preparation method
CN120809732A
Dry-method electrode membrane supported by framework membrane and preparation method
CN121237810A
